VIOLENCE AGAINST CHINESE ETHNIC GROUPS IN BATAVIA BY THE VOC (VEREENIGDE OOST-INDISCHE COMPAGNIE) IN 1740 - Ardi Tri Yuwono; Agus Budianto; Yatmin; Gijsbert ter Braake (JURNAL HISTORICA, 2025)
The tragedy of ethnic Chinese violence in Batavia (1740), known as Chinezenmoord in Dutch historiography, was one of the darkest events in the colonial history of the Dutch East Indies, in which thousands of ethnic Chinese in Batavia were massacred by VOC forces involving indigenous groups. This event not only reflects physical violence, but also the result of the VOC's discriminatory policies that create structural injustice. This research focuses on analysing the dynamics of the tragedy of the 1740 Chinese ethnic massacre in Batavia through the lens of structural violence theory and reconstructing the event using a multi-perspective approach that integrates European, Chinese, and Javanese historical sources. The research method used is a historical method with four stages, namely heuristic, source criticism, interpretation, and historiography, by utilizing historical sources, such as the VOC archive, the Kong Koan Chronicle, and the Babad Tanah Jawi. The results of the study showed that VOC policies such as residential pas, forced deportation, and economic exploitation triggered an escalation of violence, resulting in the mass murder of 10,000 ethnic Chinese. The social impact included the forced relocation of the Chinese community to Glodok and their flight to Central Java, while the political impact was in the form of a change in leadership of the Governor General of the East Indies. From an economic perspective, this tragedy caused a drastic decline in sugar production in Java.